PERSPEKTIF MASYARAKAT SITUBONDO TENTANG PENGGUNAAN TRANSAKSI MELALUI PLATFORM E-COMMERCE - Fandiyanto, Randika; Rosyadi, Yayuk Candra; Ramadhana, Virgian; Syaifulloh, Alfan; Amalia, Firdauzy; Julio, Rendy Dwi Agung; Firmansyah, Farhan Faisal (Fakultas Ekonomi dan Bisnis, 2024)
In this modern era, all technology has helped many human activities, many inventors have created ideas to create a technology or also created a system to help all human activities to meet daily needs. This system or technology is designed in accordance with all human activities, which nowadays mostly use very sophisticated cellphones, this will make it easier for the younger generation to access every system that has been created, not only the younger generation, even older people now have many updates and keep up with the times. This is proven by the large number of people, both young and old, using the internet to make it easier to communicate and access applications to fulfill their daily needs. One form of the development of information technology is an online shopping system or known as E-commerce which has been present among Indonesian people, especially the Situbondo area. Many people have used this system by accessing applications that are included in the E-commerce application, namely Shopee, Tokopedia, Lazada, Bukakapak and many more. Many people also use E-commerce for their business opportunities in selling products. Therefore, people need to understand the importance of developments in today's digital era so that they can improve their socio-economic situation. From the explanation above, it is evident that many people want to follow developments in the digital or modern era.